2012
DOI: 10.6064/2012/209896
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Pulmonary Malformation in Children

Abstract: Congenital Pulmonary Malformations (CPMs) are a group of rare lung abnormalities affecting the airways, parenchyma, and vasculature. They represent a spectrum of abnormal development rather than discrete pathological entities. They are caused by aberrant embryological lung development which occurs at different stages of intrauterine life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…BC develops from abnormal budding of tracheal diverticula and can be classified into three categories in relation to the trachea as paratracheally, intraluminally and intramurally. It can be detected as incidental finding on chest radiograph and account for 10% of the mediastinal masses in children but newborn with large cysts can develop respiratory distress, cyanosis and feeding difficulty [2]. We report a neonate with bronchogenic cyst at carina and right bronchus with respiratory distress.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…BC develops from abnormal budding of tracheal diverticula and can be classified into three categories in relation to the trachea as paratracheally, intraluminally and intramurally. It can be detected as incidental finding on chest radiograph and account for 10% of the mediastinal masses in children but newborn with large cysts can develop respiratory distress, cyanosis and feeding difficulty [2]. We report a neonate with bronchogenic cyst at carina and right bronchus with respiratory distress.…”
mentioning
confidence: 89%
“…Imperatori A et al [9] and Kamata T et al [10] observed bronchogenic cyst with pericardial defect in adult. There is a small risk of malignant transformation within the cyst; bronchoalveolar cell carcinoma and neuroblastoma are reported with bronchogenic cyst [2].…”
Section: Vol 3 Issue 1 Jan -Mar 2017mentioning
confidence: 99%
“…These result from aberrant lung development at 7 th to 17 th week of gestation resulting in cystic or solid overgrowth of tubular bronchiolar structure excluding alveoli. The incidence of CCAM (congenital cystic adenomatoid malformations) range between 1:8000 to 1:35,000 live births [1,2]. These anomalies are usually detected antenatally or postnatally in infancy and early childhood [2].…”
Section: Ccammentioning
confidence: 99%
“…The incidence of CCAM (congenital cystic adenomatoid malformations) range between 1:8000 to 1:35,000 live births [1,2]. These anomalies are usually detected antenatally or postnatally in infancy and early childhood [2].…”
Section: Ccammentioning
confidence: 99%
“…Pulmonary sequestration is a rare congenital lung anomaly defined as an area of dysplastic and nonfunctioning pulmonary tissue with an anomalous systemic blood supply and various forms of venous drainage [1] . The incidence of congenital pulmonary airway malformations is 1 per 8300 to 35,000, and pulmonary sequestrations compromise 0.15% to 6.4% of congenital lung malformations [2] . Pulmonary sequestration is primarily considered a childhood disease, as most cases are diagnosed early in life.…”
Section: Introductionmentioning
confidence: 99%